Women Nobel Peace Prize winners - Davis, Anita Price; Selvidge, Marla J., 1948- (McFarland & Company, Inc., Publishers, 2016)
"From the first woman Nobel Peace Prize recipient, Bertha von Suttner (1905), to the latest and youngest female Nobel laureate, Malala Yousafzai (2014), this book in its second edition provides a detailed look at the lives and accomplishments of each of these 16 Prize winners"--